Pengaruh Kualitas Pelayanan, Citra Perusahaan, Fasilitas Dan Lokasi Terhadap Kepuasan Konsumen (Studi Kasus Hotel Berkah Kembar Di Lampung Timur) - Suwarto, Suwarto; Fuadi, Selamet; Fitriani, Eka Lusi (Universitas Muhammadiyah Metro, 2023)
The research method used is qualitative and quantitative research. In this study, theanalytical tool used is multiple linear regression analysis to determine the dependent andindependent variables with computer program tools, namely SPSS 17 For Windows.Theresearch results are 1) Service quality variables have a positive effect on consumersatisfaction, 2) corporate image variables simultaneously affect consumer satisfaction, 3)facility variables simultaneously affect consumer satisfaction, 4) location variablessimultaneously affect customer satisfaction, 5) simultaneously variable brand image, trustand price affect consumer satisfaction at Berkah Kembar hotel.